Perlindungan Hukum Merek Ms Glow Dengan Ps Glow - Urgensi Perlindungan Hukum Merek Dagang (International Forum of Researchers and Lecturers, 2024)
Brand is an important element of a company's identity and success. As business competition becomes increasingly fierce, legal protection of brands becomes very important to maintain business continuity. This article examines the urgency of brand protection through a case study of the MS Glow and PS Glow brands. The main focus is on legal protection of brands to prevent actions that infringe intellectual property rights, avoid financial losses and maintain brand integrity. By analyzing this case, this article highlights the importance of effective laws in protecting the interests of brand owners, encouraging innovation, and ensuring fairness in a dynamic business environment.